1984
DOI: 10.1159/000183290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Furosemide and Salt Loading on Parathyroid Function in Normal Subjects

Abstract: With oral furosemide administration and salt loading, urinary calcium was significantly increased in 8 normal subjects, accompanied by parallel natriuresis. In spite of the excessive calcium loss in the urine, total and ionized serum calcium remained unchanged. All subjects had significant increases in nephrogenous cyclic AMP, suggesting that parathyroid activity is elevated in subjects with furosemide-induced hypercalciuria. With furosemide, fecal calcium was significantly decreased, and resultantly, there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…Conflicting results have been reported on the long-term effects of LD on the 24 h renal calcium excretion. Some have reported an increased calcium excretion during the first days of treatment with a subsequent return to pretreatment levels during continued therapy [17][18][19], whereas others have found a persistent increased renal calcium excretion during long-term treatment [2,5,20]. Our findings support an increased renal calcium excretion in subjects on long-term treatment with LD.…”
Section: Calcitropic Hormones and Biochemical Bone Markerssupporting
confidence: 75%
See 1 more Smart Citation
“…Conflicting results have been reported on the long-term effects of LD on the 24 h renal calcium excretion. Some have reported an increased calcium excretion during the first days of treatment with a subsequent return to pretreatment levels during continued therapy [17][18][19], whereas others have found a persistent increased renal calcium excretion during long-term treatment [2,5,20]. Our findings support an increased renal calcium excretion in subjects on long-term treatment with LD.…”
Section: Calcitropic Hormones and Biochemical Bone Markerssupporting
confidence: 75%
“…In addition to their effect on the renal and cardiovascular system, treatment with LD is known to increase the renal calcium excretion. In addition, short-term treatment with LD increases plasma parathyroid hormone (PTH) and 1,25-dihydroxyvitamin D (1,25(OH) 2 D) levels in a dose-dependent manner [2][3][4][5], and treatment with LD changes the diurnal rhythm of plasma PTH levels with an almost doubling in PTH levels a few hours after medication [6]. However, the potential effects of LD on bone mineral density (BMD) and fracture risk have only been investigated in a few studies with conflicting results [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In previously published papers describing the ability of furosemide to stimulate PTH [28,10] the more simple hypothesis was that the increase in calciuria provoked by furosemide through its action on Henle's loop would lead to transient hypocalcemia which stimulates PTH release. In line with this hypothesis, Reichel et al found that in an anuric patient, furosemide had no effect on PTH [27].…”
Section: Several Hypotheses Have Been Proposed To Explain Furosemide-mentioning
confidence: 99%
“…Several experimental and clinical studies have reported that furosemide increases plasma parathyroid hormone (PTH) after acute or chronic furosemide treatment [6,10,18]. As of today, the precise mechanism whereby furosemide stimulates PTH remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…to increase urinary excretion of Ca in humans (Castenmiller et al 1985;Shortt et al 1988). Healthy individuals who have adequate Ca and vitamin D intakes and who absorb dietary Ca efficiently adapt to high salt intakes by increasing Ca absorption to compensate for the increased urinary Ca loss (Fujita et al 1984). However, the increase in Ca absorption may not be sufficient to balance the increase in urinary Ca excretion (Breslau et al 1982).…”
Section: Calcium Supplementsmentioning
confidence: 99%